PENGARUH SELF ASSESMENT SYSTEM, SURAT TAGIHAN PAJAK DAN RESTITUSI PAJAK PERTAMBAHAN NILAI TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Cibinong Tahun 2014-2016) - Saesar Ayu Pratiwi; Elly Suryani; Kurnia Kurnia (Universitas Widyatama, 2018)
This study aims to examine the influence of Self Assessment System, Tax Refining Letter, and VAT Refund of Value Added Tax at Primary Tax Office Cibinong during 2014-2016. The data used in this research is the type of secondary data year 2014-2016. The population in this study is the data of all types of taxes at the Tax Office Pratama Cibinong. The sample selection technique used is purposive sampling. Data analysis method in this research is multiple linear regression analysis using SPSS version 23. Based on the results of the study, simultaneously Self Assessment System, Tax Refining Letters, and VAT Restitution have a significant effect on VAT revenue. While partially, Self Assessment System has a positive and significant effect on VAT revenue, Tax Refining Letters has no significant effect on VAT revenue, and VAT refund has a negative and significant effect on VAT revenue